2008 IEEE 9th Workshop on Signal Processing Advances in Wireless Communications 2008
DOI: 10.1109/spawc.2008.4641579
|View full text |Cite
|
Sign up to set email alerts
|

Fair service provision in OFDMA with partial channel-state information

Abstract: We address the problem of resource allocation on an OFDMA downlink under fairness constraints with limited Channel State Information (CSI). Target QoS corresponds to a minimum user data rate, a target bit-error rate and a maximum outage probability. The only available CSI is the channel average gain of each user. This partial CSI can be viewed as a shadowed pathloss that yields a modified user distribution on which resource allocation is based. Under these constraints, we provide the optimal resource allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Table I and Table II lists video workload parameters and OFDMA parameters for mobile WiMAX and WLAN considered for proposed network model. (1) [15], [16], [17], [20], [25], [26], [27], [35], [36], [37] where Ck,n is sub-carrier allocation indicator, Pk,n is PA indicator and Hk,n is effective sub-channel signal to noise ratio (SNR), ω is weight of the user for estimation of priority. …”
Section: Resource Allocation Scheme (Ras)mentioning
confidence: 99%
See 4 more Smart Citations
“…Table I and Table II lists video workload parameters and OFDMA parameters for mobile WiMAX and WLAN considered for proposed network model. (1) [15], [16], [17], [20], [25], [26], [27], [35], [36], [37] where Ck,n is sub-carrier allocation indicator, Pk,n is PA indicator and Hk,n is effective sub-channel signal to noise ratio (SNR), ω is weight of the user for estimation of priority. …”
Section: Resource Allocation Scheme (Ras)mentioning
confidence: 99%
“…Hence 2 subcarriers allotted to each user. We applied both Linear [15], [16], [17], [18], [19], [20] and Active-set algorithm. It is found that channel capacity achieved using Active-Set optimization is more as compared to Linear Approach.…”
Section: Algorithm For Estimating: A)mentioning
confidence: 99%
See 3 more Smart Citations